Hyaluronic acid enhancement of expanded polytetrafluoroethylene for small diameter vascular grafts - Lewis, Nicole R., author; James, Susan P., advisor; Popat, Ketul C., committee member; Bailey, Travis, committee member (Colorado State University. Libraries, 2014)
Cardiovascular disease is the leading cause of mortality and morbidity in the United States and other developed countries. In the United States alone, 8 million people are diagnosed with peripheral arterial disease per year and over 250,000 patients have coronary bypass surgery each year. Autologous blood vessels are the standard graft used in small diameter (<6mm) arterial bypass procedures. Synthetic small diameter grafts have had limited success. While polyethylene (Dacron) and expanded polytetrafluoroethylene (ePTFE) are the most commonly used small diameter synthetic vascular graft materials, there are significant limitations that make these materials unfavorable for use in the low blood flow conditions of the small diameter arteries. Specifically, Dacron and ePTFE grafts display failure due to early thrombosis or late intimal hyperplasia. With the shortage of tissue donors and the limited supply of autologous blood vessels available, there is a need for a small diameter synthetic vascular graft alternative. The aim of this research is to create and characterize ePTFE grafts prepared with hyaluronic acid (HA), evaluate thrombogenic potential of ePTFE-HA grafts, and evaluate graft mechanical properties and coating durability. The results in this work indicate the successful production of ePTFE-HA materials using a solvent infiltration technique. Surface interactions with blood show increased platelet adhesion on HA-modified surfaces, though evidence may suggest less platelet activation and erythrocyte lysis. Significant changes in mechanical properties of HA-modified ePTFE materials were observed. Further investigation into solvent selection, uniformity of HA, endothelialization, and dynamic flow testing would be beneficial in the evaluation of these materials for use in small diameter vascular graft bypass procedures.